College Students' Perception of Snacks Sold in Vending Machines in the US: A Mixed-Methods Study - Mengarelli, Cristiana Assumpção; Kirchoff, Christie; Palacios, Cristina (Frontiers in Nutrition, 2021)
Introduction: Food in vending machines in US colleges contain limited nutritious foods available for purchase, which could affect the food choices made by students leading to poor diet quality. Interventions to improve college foodscapes usually follow a top-down approach and fail to affect dietary behavioral changes ultimately. This research aims to uncover what students want and ways to achieve change. Methods: The mixed-methods approach included peer-led qualitative focus group discussions and a brief quantitative questionnaire on satisfaction from foods available in vending machines. A convenience sample of 20 students (15 females) was recruited from a Hispanic serving institution for this study. Results: Vending machines were perceived as convenient, plentiful, and unhealthy. Students expressed dissatisfaction with both the variety and nutritional quality of snacks in vending machines. Suggestions for improvement included more fresh items (fruits and vegetables) and refrigerated items with higher protein content (low-fat yogurt, hummus, and peanut butter). To implement these improvements, participants discussed the cost and feasibility of perishable items. Increasing awareness and partnering strategies were proposed to mediate potential cost and buy-in obstacles as was elevating the appeal of healthy vending machines with technological enhancements that draw customers in and educate. Conclusion and implication for practice: This group of college students was eager for positive changes in foods sold in vending machines and understand the major difficulties. The suggested changes may help this and other colleges develop policies to regulate the foods in vending machines to promote overall health and help prevent chronic diseases in the future.